Rural tourist areas for sustainable development. Community-based rural tourism in Peru - Sariego López, Ignacio (2017)
Community-based Rural Tourism (TRC) is a relatively recent experience which is developing in thecountryside, in a planned and sustainable way based on the participation of local populations organized for thebenefit of a community. Peru, as a megadiverse country, has the appropriate conditions to lead this touristic modelon a global scale, as a new form of travel, giving visitors a unique and existential experience that enhances the image of Peru as a real, competitive and high quality country. This research study presents the results obtained by the Integrated Action of the Agencia Española de Cooperación Internacional para el Desarrollo (AECID),Interuniversity Cooperation and Scientific Research Program entitled: Peru Tourist Observatory: Community-based Rural Tourism. From this standpoint, the article will offer a range of analyses of the touristic activities involving the priority community targets. The criteria followed will include geographical representation, accessibility, type of managing organization, ecological diversity, cultural diversity, origin ofthe initiative, and level of development.